2013
DOI: 10.1007/s10067-013-2356-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in detecting knee effusion with clinical examination and the effect of effusion, the patient's body mass index, and the clinician's experience

Abstract: The purpose of this study was to determine the accuracy of detecting knee effusion with clinical examination and to evaluate whether the amount of effusion, patient obesity, and the clinicians' experience affect the clinicians' decisions in patients with knee osteoarthritis. Patients presenting with knee pain were examined by two residents with different levels of experience and underwent ultrasonographic examination, including measurement of effusion in the medial, mid, and lateral aspects of the suprapatella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…While a systematic review reported that some studies have poor inter-and intrarater reliability of clinical tests of effusion (10), other studies, including ours, have reported good-to-excellent interrater reliability of knee effusion on examination (11)(12)(13). Furthermore, the predictive utility of a combination of clinical examinations for bulge sign, ballottement, and patellar tap versus ultrasound effusion has been shown to have high sensitivity and moderate specificity in senior residents (14).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…While a systematic review reported that some studies have poor inter-and intrarater reliability of clinical tests of effusion (10), other studies, including ours, have reported good-to-excellent interrater reliability of knee effusion on examination (11)(12)(13). Furthermore, the predictive utility of a combination of clinical examinations for bulge sign, ballottement, and patellar tap versus ultrasound effusion has been shown to have high sensitivity and moderate specificity in senior residents (14).…”
Section: Introductionmentioning
confidence: 62%
“…We have recently reported that physical examination effusion was highly correlated with MRI effusion, particularly moderate-to-large MRI effusion (9). Furthermore, the predictive utility of a combination of clinical examinations for bulge sign, ballottement, and patellar tap versus ultrasound effusion has been shown to have high sensitivity and moderate specificity in senior residents (14). Furthermore, the predictive utility of a combination of clinical examinations for bulge sign, ballottement, and patellar tap versus ultrasound effusion has been shown to have high sensitivity and moderate specificity in senior residents (14).…”
Section: Introductionmentioning
confidence: 97%
“…Compared to clinical examination, US is more sensitive and well correlated with the histological ndings. [6][7][8][9] Some studies reported equivalent sensitivity of synovitis detection by US compared to magnetic resonance imaging (MRI). 10,11 Moreover, this tool is non-invasive, relatively inexpensive, and involves a short examination time, as well as having no radiation burden and good patient acceptability.…”
Section: Introductionmentioning
confidence: 99%
“…As with any clinical test, clinical examination of the knee is subject to measurement error. There are, however, few studies which have formally assessed reliability in the assessment of common clinical signs for knee OA and in those studies that have reported reliability, findings have been somewhat inconsistent24,912. Some contributing factors to the inconsistency include lack of clarity and uniformity in the assessment procedures and also the grading criteria24,912.…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, few studies which have formally assessed reliability in the assessment of common clinical signs for knee OA and in those studies that have reported reliability, findings have been somewhat inconsistent24,912. Some contributing factors to the inconsistency include lack of clarity and uniformity in the assessment procedures and also the grading criteria24,912. Reliable clinical assessment is important, as poor reliability may result in misclassification in clinical and research studies of knee OA and reduce the chance of finding clinically important biological associations between clinical features of the disease and outcome or response to therapy.…”
Section: Introductionmentioning
confidence: 99%